2020
DOI: 10.1075/coll.56
|View full text |Cite
|
Sign up to set email alerts
|

Palenquero and Spanish in contact

Abstract: Bilingual speakers are normally aware of what language they are speaking or hearing; there is, however, no widely accepted consensus on the degree of lexical and morphosyntactic similarity that defines the psycholinguistic threshold of distinct languages. This book focuses on the Afro-Colombian creole language Palenquero, spoken in bilingual contact with its historical lexifier, Spanish. Although sharing largely cognate lexicons, the languages are in general not mutually intelligible. For example, Palenquero e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 230 publications
0
2
0
Order By: Relevance
“…Examples of proficiency measurements that have been used are self-report questionnaires, sociolinguistic interviews, and judgements from teachers and community leaders. With regard to characteristics that can set Palenquero heritage/L2 speakers apart from fluent adult speakers, researchers have analyzed "the usage of preverbal particles (Lipski 2020b;Smith 2013Smith , 2014, Spanish-like feminine gender agreement (Lipski 2015(Lipski , 2018b, placement and processing of the negative elements (Lipski 2010(Lipski , 2017(Lipski , 2018a, use of the pluralizer ma (Cassiani-Obeso and Smith 2021; Lipski 2012Lipski , 2014Moñino 2007Moñino , 2013Schwegler 2007b), and overall performances with interviews and translation tasks (Lipski 2020a(Lipski , 2020b)" (Lipski 2020c, p. 3).…”
Section: Bilingual Status Of the Palenquero Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of proficiency measurements that have been used are self-report questionnaires, sociolinguistic interviews, and judgements from teachers and community leaders. With regard to characteristics that can set Palenquero heritage/L2 speakers apart from fluent adult speakers, researchers have analyzed "the usage of preverbal particles (Lipski 2020b;Smith 2013Smith , 2014, Spanish-like feminine gender agreement (Lipski 2015(Lipski , 2018b, placement and processing of the negative elements (Lipski 2010(Lipski , 2017(Lipski , 2018a, use of the pluralizer ma (Cassiani-Obeso and Smith 2021; Lipski 2012Lipski , 2014Moñino 2007Moñino , 2013Schwegler 2007b), and overall performances with interviews and translation tasks (Lipski 2020a(Lipski , 2020b)" (Lipski 2020c, p. 3).…”
Section: Bilingual Status Of the Palenquero Speakersmentioning
confidence: 99%
“…Adult speakers of Palenquero (almost) always use ma to mark plural contexts (Cassiani-Obeso and Smith 2021), while L2 speakers often extend ma indiscriminately to singular as well as plural referents (Lipski 2020c). A variety of production tasks (e.g., picture naming, written assignments, sociolinguistic interviews) have also provided evidence for the overextension of ma by younger speakers (Lipski 2012(Lipski , 2014(Lipski , 2015(Lipski , 2020a(Lipski , 2020bDeibel 2020). It has been suggested that younger speakers may not recognize the function of ma as a plural marker (Lipski 2020c, p. 5).…”
Section: At Schoolmentioning
confidence: 99%